Analisa faktor yang berpengaruh pada volume ekspor komoditas kopi Jawa Timur (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of the study is to analyze the factors that affect the export volume of coffee commodities in East Java related to the influence of the US dollar exchange rate, domestic prices, export prices and production on export volumes both partially and simultaneously before Covid-19 and during Covid-19 . The results of the study from 58 samples showed that the USD exchange rate, domestic price, export price, and production simultaneously had a significant effect on export volume before Covid-19 and had no effect during Covid-19. Partially, the results showed that the USD exchange rate had a negative and insignificant effect on export volume before and during Covid-19. Domestic prices have a positive and significant effect on export volume before Covid-19 but during Covid-19 it does not have a significant effect. Meanwhile, export prices have a positive and significant effect on export volume before Covid-19, but during Covid-19 it has a negative and insignificant effect. The results of the study also illustrate that production has a positive but not significant effect during Covid-19 and a negative and insignificant effect during Covid-19. Keywords: USD Exchange Rate, Domestic Prices, Export Prices Production On The Volume Of Exports